2011
DOI: 10.1111/j.1567-1364.2011.00760.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and physiological aspects of alcohol dehydrogenases in the ethanol metabolism of Saccharomyces cerevisiae

Abstract: The physiological role and possible functional substitution of each of the five alcohol dehydrogenase (Adh) isozymes in Saccharomyces cerevisiae were investigated in five quadruple deletion mutants designated strains Q1-Q5, with the number indicating the sole intact ADH gene. Their growth in aerobic batch cultures was characterised in terms of kinetic and stoichiometric parameters. Cultivation with glucose or ethanol as carbon substrate revealed that Adh1 was the only alcohol dehydrogenase capable of efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 58 publications
4
63
1
Order By: Relevance
“…One of the obvious strategies to lower ethanol production is to decrease the activity of the main enzyme responsible for ethanol formation. Deletion of ADH1, which encodes alcohol dehydrogenase, has been shown to decrease ethanol production in laboratory yeast strains (9,12,13). In the present work, however, deletion of ADH1 did not affect ethanol formation, suggesting that other alcohol dehydrogenase isozymes compensate for loss of this enzyme in AWRI1631 wine yeast background under the conditions used in this study.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…One of the obvious strategies to lower ethanol production is to decrease the activity of the main enzyme responsible for ethanol formation. Deletion of ADH1, which encodes alcohol dehydrogenase, has been shown to decrease ethanol production in laboratory yeast strains (9,12,13). In the present work, however, deletion of ADH1 did not affect ethanol formation, suggesting that other alcohol dehydrogenase isozymes compensate for loss of this enzyme in AWRI1631 wine yeast background under the conditions used in this study.…”
Section: Discussioncontrasting
confidence: 53%
“…In the present work, however, deletion of ADH1 did not affect ethanol formation, suggesting that other alcohol dehydrogenase isozymes compensate for loss of this enzyme in AWRI1631 wine yeast background under the conditions used in this study. Indeed, Adh3p has been shown to mimic the function of Adh1p in a genetic background lacking ADH1, ADH2, ADH4, and ADH5 (12). However, deletion of both ADH1 and ADH3, together and individually, had no effect on ethanol production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extracellular acetaldehyde concentrations in the adh1⌬ mutant (2,402 M OD 600 unit Ϫ1 ) were 6-fold higher than those in the wild type (390 M OD 600 unit Ϫ1 ). In addition, previous reports have indicated that deleting ADH1 increased the extracellular acetaldehyde level (37). The ADH1 gene encodes alco-hol dehydrogenase 1, and the enzyme is responsible for catalyzing the formation of ethanol from acetaldehyde during alcohol fermentation.…”
Section: Resultsmentioning
confidence: 99%